Prediksi Prestasi Siswa SMAN 1 Muntok Berdasarkan Motivasi, Kedisiplinan, dan Sosial Ekonomi dengan Naïve Bayes - Endraswari, Putri Mentari; Tou, Nurhaeka (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This study aims to predict the achievement of class X students at SMA Negeri 1 Muntok by classifying socio-economic data (parents' income), student learning motivation, and student discipline using the Naive Bayes machine learning method. The approach taken in this study is quantitative, with a total of 104 students from 286 class X students who have gone through the data cleansing stage. Data collection was carried out through distribution and documentation. The Naïve Bayes method is used as a prediction analysis technique with the Python programming language. This study shows that the use of this method has an accuracy of 71%, with the prediction results of socio-economic variables, motivation, and discipline on student achievement showing that the discipline variable shows a stronger correlation with student achievement, compared to other variables.